Tax Avoidance through E-Commerce and Cross-Border Shopping - Benjamin Harbolt (Center for Economic Studies and ifo Institute (CESifo), 2019)
As e-commerce has grown over the last few decades so has states' concern for its use for sales tax avoidance. Using a panel of Washington State tax jurisdictions from 2005 through 2015, I estimate the effect of a sales tax regime change on the elasticities of taxable sales. I find the regime change, targeted at reducing sales tax avoidance through remote purchases, had a differential impact that varied by tax jurisdiction. I find that in tax jurisdictions near the border of lower-sales-tax states (Oregon and Idaho) consumers became more responsive to the difference in sales tax rates across borders than their counterparts in the interior of the state. I interpret this as a substitution by consumers along the Oregon and Idaho border from e-commerce purchases to cross-border shopping in order to avoid sales taxes.
Keywords: H26; H71; 330; sales tax avoidance; destination-based taxation; cross-border shopping